Physics Practical Performance Through Differentiated Instruction: Insight into Senior High School Physics Practical Instruction in Ghana - Mustapha Issahaku; George Oduro-Okyireh; Isaac Owusu-Mensah (Journal of Research in Education and Pedagogy, 2026)
Recurring challenges in the physics practical performance of Ghanaian Senior High School (SHS) students, particularly in basic experiments like the simple pendulum, warrant fresh pedagogical approaches. Differentiated Instruction (DI), which tailors instruction to different learner needs, is a promising yet unexplored strategy in this context. This study aimed to establish the learning needs of selected SHS students in performing the simple pendulum experiment and pinpoint some DI strategies that enhance their practical performance. A quasi-experimental design was employed involving 160 Form 2 physics students (97 males and 63 females) drawn from two intact classes in two senior high schools in Ghana. A structured questionnaire manifested significant learning issues: 78.7% of the students lacked a clear conceptualisation of the relationship between pendulum length and period, with recording time (28.8%), graphing results (24.4%), and period calculation (23.8%) being primary issues. Furthermore, 53.1% felt uneasy with mathematical equations, and 79.4% lacked confidence to conduct the experiment individually. The experimental group (n=80) received a four-week DI intervention. Regression analysis of post-intervention data indicated five DI strategies that predicted improved performance: hands-on experimentation (β = 0.449, p < .000), teacher modification of learning styles (β = 0.192, p = .018), decreased complexity of lessons (β = 0.175, p = .022), students feeling comfortable demonstrating knowledge via experiments (β = 0.157, p = .025), and offering choices for assignments (β = 0.177, p = .016). A Mann–Whitney U test revealed that the DI group achieved significantly higher post-test scores compared to the control group (U = 3193.50, Z = –0.023, p = .982), with a medium-to-large effect size (r = .41). The study concludes that senior high school students exhibit diverse learning needs in physics practicals, which can be effectively addressed through adaptable and flexible differentiated instructional approaches. It recommends integrating these evidence-based interventions into teacher education and curriculum design to improve physics practical performance.